Investigation for gold and base metals mineralization and petrochemical characteristics of the rocks of upper parts of Bagrot valley, Gilgit-Baltistan, Pakistan - Miandad, Sadaf; Shah, Mohammad Tahir; Danishwar, Shuhab Khan; Ahmad, Laeiq (Journal of Himalayan Earth Sciences, 2014)
Occurrence of placer gold has been reported in the stream sediments of the Gilgit-Baltistan for long time. Recent geochemical surveys in this region identified some areas with high concentration of gold. Bagrot valley (the study area), is one of these anomalous catchments situated in northeast of Gilgit, the capital city, of Gilgit-Baltistan province of Pakistan. The study area consists of rocks of Cretaceous Chalt Volcanic Group (CVG) and gabbroic-diorites of Kohistan batholiths (KB) belonging to the Kohistan island arc. The rocks of the CVG are mainly composed of porphyritic (basalts) and non-porphyritic (basalts to basaltic-andesite) volcanics. The porphyritic volcanics are hypersthenes normative with high plagioclase (Ab+An) normative composition whereas the non-porphyritic volcanics have greater amount of normative pyroxene (Hy+Di) relative to plagioclase (Ab+An). These are strongly deformed, highly tectonized and are metamorphosed mainly to greenschist facies and lesser extent to epidote-amphibolite facies. Numerous sulfide-baring altered/sheared zones are prominent along local faults within the rocks of CVG. These zones contain, pyrite, chalcopyrite and limonite and hydrothermal alteration products such as chlorite, epidote, sericite, kaolinite and trimolite/sctinolite. The hydrothermally altered zones and the host rocks are the focus of this study for possible gold, silver and base metal mineralization and their petrochemical characteristics. The enrichment and depletion factors of various metals such as Au, Ag, Cu, Pb, Zn, Ni and Cr in the sulfide-bearing altered/sheared zone suggest the enrichment of Au, Ag and Pb while rest of the metals are depleted. This can be attributed to the immobile nature of Au, Ag and Pb and mobile nature of other metals during hydrothermal alteration. The multi-element spidergrams of both porphyritic and non-porphyitic volcanics of the CVG and the gabbroic-diorites show enrichment of LILE relative to HFSE with negative anomaly of Nb. The whole rock geochemistry of the studied non-porphyritic volcanics of CVG and the gabbroicdiorites of KB are of typical calc-alkaline character showing close affinities to subduction zone geochemical component. The porphyritic volcanics of the CVG exhibit tholeiitic character but are also consistent with the island arc tectonic setting.